2020
DOI: 10.1139/apnm-2019-0700
|View full text |Cite
|
Sign up to set email alerts
|

Blood flow restriction impairs the inflammatory adaptations of strength training in overweight men: a clinical randomized trial

Abstract: The aim of this study was to evaluate the impact of high-intensity strength training (ST) or low-intensity strength training with blood flow restriction (ST-BFR) on monocyte subsets, the expression of C-C chemokine receptor 5 (CCR5), and CD16 on monocytes, and tumor necrosis factor alpha (TNF-α) production of overweight men. Thirty overweight men were randomly assigned to conventional ST or ST-BFR. Both groups performed exercises of knee extension and biceps curl with equal volume (3 sessions/week) over 8 week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…The authors showed an increase in the population of intermediate monocytes only in overweight but not in obese individuals, with no changes in the percentage of monocytes expressing TLR-4. Additionally, after traditional strength training or with flow restriction (4 sets of 23 repetitions at 30 % of 1-RM), sedentary overweight in-dividuals showed beneficial effects on monocyte subtypes [86]. In this study, there was a reduction in the percentage of non-classical monocytes and expression of CD16 in CD14 + monocytes, as well as an increase in the percentage of classical monocytes only in the group that performed the traditional training.…”
mentioning
confidence: 45%
“…The authors showed an increase in the population of intermediate monocytes only in overweight but not in obese individuals, with no changes in the percentage of monocytes expressing TLR-4. Additionally, after traditional strength training or with flow restriction (4 sets of 23 repetitions at 30 % of 1-RM), sedentary overweight in-dividuals showed beneficial effects on monocyte subtypes [86]. In this study, there was a reduction in the percentage of non-classical monocytes and expression of CD16 in CD14 + monocytes, as well as an increase in the percentage of classical monocytes only in the group that performed the traditional training.…”
mentioning
confidence: 45%
“…It is possible that methodological differences (e.g. gating strategy, anticoagulant, monocyte selection, staining techniques) or even unanticipated human pre-existing conditions 56,57 could account for some of these differences. The relative frequency of CD16− and CD16+ monocytes before and after plasma-free homeostatic extravasation confirmed that both adult and newborn CD16+ monocytes are preferential extravasators in our vascular model.…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed an increase in the population of intermediate monocytes only in overweight but not in obese individuals, with no changes in the percentage of monocytes expressing TLR-4. Additionally, after traditional strength training or with flow restriction (4 sets of 23 repetitions at 30% of 1-RM), sedentary overweight individuals showed beneficial effects on monocyte subtypes 86 . In this study, there was a reduction in the percentage of non-classical monocytes and expression of CD16 in CD14 + monocytes, as well as an increase in the percentage of classical monocytes only in the group that performed the traditional training.…”
Section: Type Of Exercise and Intensity As Key Variable On Monocytes ...mentioning
confidence: 95%
“…In this study, there was a reduction in the percentage of non-classical monocytes and expression of CD16 in CD14 + monocytes, as well as an increase in the percentage of classical monocytes only in the group that performed the traditional training. The benefits of these changes were confirmed by reduction in the production of TNF-α with or without LPS stimulation [86]. On the other hand, the phagocytosis index and production of reactive oxygen species were not altered in PBMCs of sedentary individuals after traditional strength training [87].…”
mentioning
confidence: 93%